PENENTUAN DERAJAT LUKA BERDASARKAN METODE EVALUATION OF IMPAIRMENT PADA REKAM MEDIS PASIEN RUMAH SAKIT BHAYANGKARA PROVINSI RIAU PERIODE JANUARI-DESEMBER 2012 - Aisyah, Siti; Afandi, Dedi; Burhanuddin, Laode (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Visum et Repertum on living sacrifice is a written report made by physicians at the request of investigators on the case of injury in living sacrifices were examined for the benefit of the judiciary. The injury on someone can result in a defect (impairment) a capacity to do the work everyday. To assess the level of decline or the disability can be used at a reduced rate of assessment methods or disability (evaluation of impairment method). The aim of this study was to find an effective method in determining the degree of qualification were on VeR by assessing WPI (Whole Person Impairmernt) victims contained in the medical record. This descriptive retrospective study was done since March 2014 at Bhayangkara Hospital Riau Province. Based on the results of this study was found the largest of age group 25-44 years old (52,46%) had violence, and most commonly happened in men (55,86%). Types of injuries most commonly found was hematom (66,6%) and the most type of violence was blunt force injury (92,6%). The most common degree of the injury was the first degree (93,20%).Key words: Visum et Repertum, evaluation of impairment, AMA Guides